For x + y + z = π , if tan x tan z = 2 and tan y tan z = 1 8 , find the value of tan 2 z .
This problem is part of the set Trigonometry .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is not true that tan x = 2 1 . Do you see where he made the error?
Can someone prove that tan x + tan y + tan z = tan x tan y tan z ?
For x + y + z = π , we know that cot x cot y + cot y cot z + cot x cot z = 1 Given tan x tan z = 2 and tan y tan z = 1 8 , we get cot x cot z = 2 1 and cot y cot z = 1 8 1 . Hence,
cot x cot y + 1 8 1 + 2 1 = 1 cot x cot y + 9 5 = 1 cot x cot y = 9 4
Now, we have the following equations. cot x cot y = 9 4 cot y cot z = 1 8 1 cot z cot x = 2 1 We shall solve these simultaneously to find the value of cot z .
cot x = 2 cot z 1 a n d cot y = 1 8 cot z 1 ∴ ( 2 cot z 1 ) ( 1 8 cot z 1 ) = 9 4 3 6 cot 2 z 1 = 9 4 cot 2 z 1 = 1 6 tan 2 z = 1 6
Given that { tan x tan z = 2 tan y tan z = 1 8 . . . ( 1 ) . . . ( 2 )
( 1 ) ( 2 ) : tan x tan z tan y tan z = tan x tan y = 2 1 8 = 9 ⟹ tan y = 9 tan x
Since x + y + z = π :
⟹ tan x tan y tan z 1 8 tan x ⟹ tan z = tan x + tan y + tan z = tan x + 9 tan x + tan z = 8 tan x Given that tan y tan z = 1 8 Note that tan y = 9 tan x
Now consider,
tan z ⟹ tan z 8 tan x 4 3 6 tan 2 x − 4 tan 2 x ⟹ tan 2 z = tan ( π − x − y ) = − tan ( x + y ) = − 1 − tan x tan y tan x + tan y = 9 tan 2 x − 1 tan x + 9 tan x = 9 tan 2 x − 1 5 = 5 = 4 1 = ( 8 tan x ) 2 = 6 4 × 4 1 = 1 6 Since x + y + z = π and tan ( π − θ ) = − tan θ tan z = 8 tan x
Problem Loading...
Note Loading...
Set Loading...
F o r x + y + z = π , w e k n o w t h a t t a n x + t a n y + t a n z = t a n x × t a n y × t a n z W e k n o w t a n x × t a n z = 2 ∴ t a n x + t a n y + t a n z = 2 t a n y = > t a n x + t a n z = t a n y − > e q ( 1 ) W e k n o w t a n y × t a n z = 1 8 ∴ t a n x + t a n y + t a n z = 1 8 t a n x = > t a n y + t a n z = 1 7 t a n x − > e q ( 2 ) F r o m e q ( 1 ) a n d e q ( 2 ) , w e g e t t a n z = 8 t a n x ∴ t a n x = 2 1 = > t a n z = 4 ∴ t a n 2 z = 1 6